Pengaruh Customer Perceived Value Dan Trust Terhadap Loyalitas Pengguna Mobile Banking Dengan Kepuasan Sebagai Variabel Intervening Pada Bank Syariah Indonesia : (Studi Kasus Mahasiswa Universitas Islam Negeri Sumatera Utara) - Rahmansyah Rahmansyah; Marliyah Marliyah; Atika Atika (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to analyze the influence of Customer Perceived Value and Trust on Loyalty of mobile banking users with Satisfaction as an Intervening Variable at Bank Syariah Indonesia among UIN North Sumatra Students. The sampling technique in this research used purposive sampling. Data collection was carried out by distributing questionnaires to 100 respondents. The data analysis method used is path analysis with SPSS 25 software. The results of this research show that partially, customer perceived value and trust have a direct effect on satisfaction. customer perceived value, trust and satisfaction have a direct effect on loyalty. Simultaneously, customer perceived value and trust have a direct effect on satisfaction. customer perceived value, trust and satisfaction also have a direct influence on loyalty. Satisfaction has a significant effect as a mediator of the relationship between customer perceived value and loyalty. Satisfaction also has a significant effect as a mediator of the relationship between trust and loyalty.